Mechanisms controlling arrangements and movements of nuclei in pseudostratified epithelia - Lee, Hyun O.; Norden, Caren (Trends in cell biology, 2013)
During development, cells undergo complex rearrangements that contribute to the final tissue architecture. A characteristic arrangement found in rapidly expanding, highly proliferative tissues is pseudostratified epithelium, which features notably elongated cells with varied nuclear positions along the cell axis. Although anomalies in its structure are implicated in diseases like microcephaly, how pseudostratification is formed and maintained remains elusive. In this review, we focus on a typical feature of pseudostratified epithelia called interkinetic nuclear migration (INM), which describes dynamic movements of nuclei within the elongated cell bodies. We provide an overview of cytoskeletal components underlying INM in different systems, discuss current understanding of its kinetics and timing, and evaluate how conflicting results could be explained through developmental and evolutionary considerations.